PENDAMPINGAN PENERAPAN SISTEM AKUNTANSI KAS PADA UMKM DI NAGORI SILAU BAYU - Liza Novianti; Khaidir Ali (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) have considerable potential to develop in the current digital era as well as to support the country's economy. However, until now there are still many MSMEs that have not implemented a cash accounting system in their business. The purpose of the Assistance for the Implementation of the Cash Accounting System for MSMEs in Nagori Silau Bayu is to assist MSMEs in managing cash records (journals of cash receipts and disbursements) in accordance with the applicable cash accounting system. The methods used in this activity are the preparation stage (preparing the material to be socialized), the introduction stage (excavating information on the use of cash records), and the implementation stage (explaining materials, training, mentoring, and guidance) in implementing the cash accounting system for MSMEs in Nagori Silau Bayu. The results of this study are MSME actors in Nagori Silau Bayu have understood the material that has been socialized in the form of the practice of making journal receipts and cash disbursements, distinguishing between debits and credits in a journal. The importance of the results obtained is to record receipt transactions such as cash sales transactions and other activities that directly affect cash.